Faith for the times ; pt 1 studies in the prophecy of Isaiah chapters 40 to 66 - Redpath, Alan (London, UK : Pickering and Inglis, 1972)
Contents : pt 2 : The promise of deliverance.
Keywords: Bible -- criticism, interpretation, etc